Le chômage et ses calendriers - Léa Lima (Temporalités)
Programs to support the unemployed can be read as an institutionally prescribed time, measured, optimized, and less oriented towards exiting unemployment than towards rehabilitating employability. We are interested in the action logics that govern the construction of standards for timetables for access to supported employment characterized by duration, sequencing, and spacing between socially defined events as a component of the time of employability. The specific time of the support and its programs then appears as an object of expert knowledge of various kinds produced by socio-economic engineers on the one hand and managers of the activity of employment counselors on the other.